Environmental and socioeconomic criteria to prioritize investments in the road network of Costa Rica - Arias García, Rodrigo (2025)
Given the absence of a formal implementation of a Pavement Management System for the National Paved Road Network of Costa Rica, there are no long-term planning processes of investments in the pavements. The research presented herein aims to demonstrate, in addition to the feasibility of perform long-term investment plans (20 years), that prioritization criteria on environmental, social and economical aspects can be included in the plan.For the preparation of investment plans, the condition of the pavement was estimated through an index composed of functional capacity and structural capacity in each section of the National Road Network. Each of these sections contains characteristicsreferring to traffic, route hierarchy and others. Subsequently, costs of maintenance techniques are estimated using contract 2014LN-000018-0C00.Through Woodstock software, linear optimization techniques were used to carry out investment scenarios incorporating different prioritization criteria. In this way, the Social Progress Index, the Cantonal Competitiveness Index and the CO2 emission are used as criteria to prioritize investments in the sections of the National Paved Road Network of Costa Rica.With the results, it is possible to confirm the feasibility of preparing longterm investment plans based on the inputs available in Costa Rica. In addition, it is observed that the budget increases have a greater effect on the lapse with which a better condition of the pavements is achieved than in the condition itself. Likewise, the reduction of CO2 emissions will have an impact on the condition of the network, since reconstruction interventions are those that require activities with a higher emission of pollutants.